Rabies post-exposure prophylaxis in the Philippines: health status of patients having received purified equine F(ab')(2) fragment rabies immunoglobulin (Favirab). - Beatriz P Quiambao; Hazel Z Dytioco; Ruby M Dizon; Marilyn E Crisostomo; Thelma M Laot; Dirk E Teuwen (Public Library of Science (PLoS), 2008)
BACKGROUND: Recommended treatment for severe rabies exposure in unvaccinated individuals includes wound cleaning, administration of rabies immunoglobulins (RIG), and rabies vaccination. We conducted a survey of rabies treatment outcomes in the Philippines. METHODS: This was a case series involving 7,660 patients (4 months to 98 years of age) given purified equine RIG (pERIG) at the Research Institute for Tropical Medicine (Muntinlupa, Philippines) from July 2003 to August 2004 following Category II or III exposures. Data on local and systemic adverse reactions (AR) within 28 days and biting animal status were recorded; outcome data were obtained by telephone or home visit 6-29 months post-exposure. RESULTS: Follow-up data were collected for 6,464 patients. Of 151 patients with laboratory-confirmed rabies exposure, 143 were in good health 6-48 months later, seven could not be contacted, and one 4-year-old girl died. Of 16 deaths in total, 14 were unrelated to rabies exposure or treatment. Two deaths were considered PEP failures: the 4-year old girl, who had multiple deep lacerated wounds from a rabid dog of the nape, neck, and shoulders requiring suturing on the day of exposure, and an 8-year-old boy who only received rabies PEP on the day of exposure. CONCLUSIONS: This extensive review of outcomes in persons with Category III exposure shows the recommended treatment schedule at RITM using pERIG is well tolerated, while survival of 143 laboratory-confirmed rabies exposures confirms the intervention efficacy. Two PEP intervention failures demonstrate that sustained education and training is essential in rabies management.